PEREMPUAN SEBAGAI OBJEKTIFIKASI DALAM NOVEL THE VEGETARIAN KARYA HAN KANG: TINJAUAN FEMINIS EKSISTENSIAL SIMONE DE BEAUVOIR - Indral Waldi; Iswadi Bahardur; Wahyudi Rahmat (STKIP Pesisir Selatan, 2025)
One of the important aspects often raised in literary works is gender representation, particularly that of women. Within the structure of a patriarchal society, women are frequently positioned as the Other or as subordinate parties, confined to the domestic sphere and portrayed as passive or emotional. This study discusses the issue of women as the Other in Han Kang’s novel The Vegetarian from the perspective of Simone de Beauvoir’s existentialist feminism. This novel was chosen because it depicts a female character, Yeong-hye, who is positioned as the Other from a male perspective. The study employs a qualitative method with a descriptive-analytical approach, using data sources in the form of quotations from the novel, and data collection techniques through close reading and note-taking, which were then analyzed using Beauvoir’s existentialist feminist theory. The findings indicate that Yeong-hye is constructed as the Other through acts of objectification and subordination by men, which reinforce patriarchal dominance in controlling women’s bodies and negating their subjectivity. Literature can serve as both a reflective and critical medium to highlight social realities, including gender injustice, as well as offer alternative perspectives on women’s freedom and identity.